Identifikasi Bencana Rob dan Pengaruhnya Pada Kerentanan Sosial di Kecamatan Semarang Utara Kota Semarang - Vica Gitya Haryanti; Nany Yuliastuti (Universitas Diponegoro, Indonesia, 2021)
Coastal innudation which is still happening today in the coastal area of Semarang City has caused the affected area to become socially vulnerable. This study aims to identify the effect of coastal innudation on conditions of social vulnerability in North Semarang District, Semarang City. The method used in this study is a quantitative method using quantitative descriptive analysis techniques and scoring analysis. The analysis was carried out using descriptive analysis of the condition of coastal innudation which caused social vulnerability and scoring analysis which resulted in the level of social vulnerability in the District of North Semarang. The result of this research is that the coastal innudation in North Semarang District affects social vulnerability which is classified into 3 categories, namely high, medium and low social vulnerability. High social vulnerability dominates the social vulnerability value in North Semarang Sub-District because 4 out of 9 urban villages in North Semarang Sub-District have a high vulnerability value due to coastal innudation.